Perkuatan Sambungan Perpanjangan Batang Kayu Ulin Dengan Kombinasi Baut Dan Perekat Epoxy - Bambang Sugiarto; Fakhri Fakhri; Alfian Kamaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In this paper, to strengthen the connection between wood joints is conducted by the use of combination of bolt and epoxy adhesives. There where three variations of connection observed in this study e.g; U1, U2, U3. U1 was using a bolt connecting device. U2 was using a bolt connectors which is reinforced with epoxy adhesive on the bolt hole. U3 was using a bolt connectors which is reinforced with 40 MDGL epoxy adhesives in the joint slice plane. The result of this study indicates that the bolt connection yielding mode is theoretically as same as the yielding mode that occurs in the result of laboratory testing, named mode IIIs. The lateral resistance of bolt joints form laboratory tests result is 108% greater compared to the lateral resistance of bolt joints theoretically. The addition of epoxy adhesive to the bolt hole does not provide the real reinforcement of the joint extension of Ulin Woods with bolt connecting tools. The addition of epoxy adhesives with the amount of 40 MDGL in the joint slice plane, provides 16.6% reinforcement on the joint extension of Ulin Woods with bolt joint tools.Keywords: reinforcement joints, bolt joints, epoxy adhesive joints, lateral resistance